Mental Distress and Psychological Disorders Related to COVID-19 Mandatory Lockdown - Kakaje, Ameer; Fadel, Ammar; Makki, Leen; Ghareeb, Ayham; Al Zohbi, Ragheed (Frontiers in Public Health, 2021)
Background: Restrictions that were enforced from COVID-19 have affected many people’s lifestyles and ability to earn. They caused a distress that added further stress to the Syrian population who had endured 9 years of war. This study aims to assess this distress and the major concerns of the people related to COVID-19. Methods: Online questionnaires were distributed using SPTSS, K10, and MSPSS which were used with other demographic, war- and COVID-19-related questions that were taken from The (CRISIS) V0.1 Adult Self-Report Baseline Form. Results: Our sample included 5588 with the mean age of 26.84 ± 7.815 years. Of those, only one case of COVID-19 was confirmed. Over 42.7% had two or more positive PTSD symptoms, 42.6% had moderate or severe mental disorder, but only 14.9% had low social support. Higher PTSD and K10 scores overall were seen in females and with most of war variables (P<0.05). Relationship with partner were negatively affected in most and distress from the declined ability to work and provide food were the most prominent. Conclusions: The indirect effect of COVID-19 is far more than that of the pathogen itself. Reduced ability to earn and to provide food were the main concerns. Relationships deteriorated in participants with high K10 and PTSD scores who also had more symptoms and used more hypnotics in the last 4 weeks. Smoking changes were not related to K10 and PTSD. Social support played a role in reducing stress, but with the relationships being affected, lower support was observed.